The Impact of Organizational Culture Towards Organizational Citizenship Behavior Through Job Satisfaction and Competency Among Online Media Employees - Rina Anindita; Nandya Putri Bachtiar (Universitas Trisakti, 2021)
The objective of this research is to identify whether the organizational culture becomes the correct foundation to increase organizational citizenship behavior with work satisfaction and competency. This research is expected to become a reference for the next research about the impact of organizational culture on organizational citizenship behavior based on work satisfaction and competency. On top of that, this research is expected to provide valuable information so it can become a base study or consideration for a company, especially in the media industry to effectively manage its human resources. Media industry have a unique character because they give freedom to their employee to make them get used to multitasking. Therefore, it needed support from an external factor which is to create a good organizational culture that will create work satisfaction and develop competencies as well as improve OCB behavior among employees. This research is conducted by using questioners with 245 respondents that work in online media from December to January 2020. The data has been analyzed by using Structural Equation Model (SEM). The result of this research shows that there is a relationship between organizational culture the work satisfaction among the employee of the online media industry. Furthermore, there is a relationship between organizational culture towards employee competency in the online media industry and it also shows a relation between work satisfaction towards organizational citizenship behavior in online media industry employees. Lastly, the result also shows a relation between competency towards organization citizenship behavior in online media industry employees. On the other hand, work satisfaction and competency also mediate the relation between organizational culture and organizational citizenship behavior.